Reading Difficulties of EFL Students: A Case Study of First-Year Student of English Language Education FKIP UIR - Marhamah Ahmad Hamid; Yulianto Yulianto (Department of English Language Education, UIN Sunan Ampel Surabaya, 2022)
Student skill of Reading or understanding text considered as one of four fundamental language skills which means EFL student have to obtain a good level of reading. Actually, reading skill is not an easy skill to be mastered of, since still much students carried out with reading problem. The aim of this research is to examine reading difficulties that first-year student of English Language Education deal with, and to identify students reading problems and the reasons behind their weaknesses of reading assignment. This research used qualitative research method; it used to obtain data of reading comprehension difficulties faced by first year student of English Language Education FKIP UIR. As research instruments, it used questionnaire which contains of seventeen multiple types of questions which divided into four parts. The result of this research indicated that based on the analysis, first year students do not able on having fluent reading, because students currently deal with various reading difficulties. It can be concluded that Students have to be provided with appropriate teaching strategies depends on learning styles and students’ needs. Thus, the final product of this research is a book of reading for the first year students of English language Education of FKIP-UIR.